2008
DOI: 10.1177/0091270007310382
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a Pharmacokinetic Effect of Raltegravir on Midazolam: In Vitro/In Vivo Correlation

Abstract: Raltegravir is a novel HIV-1 integrase inhibitor with potent in vitro activity (95% inhibitory concentration = 33 nM in 50% human serum). In vitro characterization of raltegravir inhibition potential was assessed against a panel of cytochrome P450 (CYP) enzymes. An open-label, 2-period study was conducted to assess the effect of raltegravir on the pharmacokinetics of midazolam, a sensitive CYP 3A4 probe substrate: period 1, 2.0 mg of midazolam; period 2, 400 mg of raltegravir every 12 hours for 14 days with 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 8 publications
4
56
0
Order By: Relevance
“…RAL is not a cytochrome P450 (CYP450) substrate and does not interact with midazolam in vitro and in vivo (8). Metabolism of RAL is dependent on the activity of UDP-glucuronosyltransferase 1A1 (UGT1A1) (11).…”
mentioning
confidence: 99%
“…RAL is not a cytochrome P450 (CYP450) substrate and does not interact with midazolam in vitro and in vivo (8). Metabolism of RAL is dependent on the activity of UDP-glucuronosyltransferase 1A1 (UGT1A1) (11).…”
mentioning
confidence: 99%
“…A 2-period study assessed the influence of raltegravir (800 mg/day) on the pharmacokinetics of midazolam (single 2-mg oral dose), a marker of CYP3A4 activity (Class II). 22 Midazolam AUC and C max in the presence and absence of raltegravir remained within bioequivalence limits, suggesting that raltegravir does not affect CYP3A4 activity.…”
mentioning
confidence: 87%
“…In vivo and in vitro studies using isoform selective chemical inhibitors and cDNA-expressed UGTs showed that UGT1A1 is the primary enzyme responsible for the formation of raltegravir-glucuronide (87) (Merck & Co, 2007;Kassahun et al, 2007). In vitro studies demonstrate that raltegravir is not a substrate for cytochrome P450 (CYP) enzymes and does not inhibit CYP1A2, 2B6, 2C8, 2C9, 2C19, 2D6, or 3A or induce 3A4 (Iwamoto et al, 2008). Similarly, raltegravir is not an inhibitor of UGTs (UGT1A1 and UGT2B7) or P-glycoprotein (P-gp)-mediated transport (Merck & Co, 2007).…”
Section: Integrase Inhibitors (Inis)mentioning
confidence: 99%